The Difference between Articulate and Interactive Power Point as TPACK Supporting Technology to Improve Analysis Ability of Nervous System Subjects - Penti Risanti Dewi; Nia Nurdiani; Cartono (Biosfer : Jurnal Biologi dan Pendidikan Biologi, 2023)
Since COVID-19 pandemic, online learning is constrained because knowledge of technology for education still lacking. So it can’t be used in varies way and makes learning feels monotonous, saturated, and cognitive ability such analytical are unsatisfactory. This study intends to compare the effectiveness of using interactive multimedia (IMM) developed with Articulate and Power Point in TPACK-based learning to improve students' analytical skills on nervous system material. The method is quasi-experimental and nonequivalent control group design. The sample was selected from class XI MIPA A and XI MIPA C at SMA Angkasa Lanud Husein Sastranegara through purposive sampling technique, 23 students in each class. The data was obtained from response questionnaires and question items, dominated by C4 which were redefined into distinguishing, organizing, and attributing problems. The results showed that normalized N-Gain in high category dominated the other categories in Articulate class (52% of students) and interactive Power Point class (43% of students). There was no significant difference in increasing analytical ability between Articulate class and interactive Power Point class (0.760 > 0.05). Based on the results, it can be concluded that IMM which was developed with Articulate and Power Point improves ability of analyzing nervous system material while online learning.